Efficacy of Using a Vessel Dilator during Surgery to Evaluate Vein Diameter and Predict Radiocephalic Arteriovenous Fistula Maturation and Patency - Kanako Takai; Takehisa Nojima; Hidehiko Taguchi; Kosei Hasegawa; Takashi Yamauchi (Surgeries)
Background: We use vessel dilators to assess the diameter of the target vein during surgery for arteriovenous fistula (AVF) creation in hemodialysis patients. This study investigates the efficacy of using vein diameter as measured using dilators (surgical diameter; SD) versus that as measured by preoperative ultrasonography (ultrasonographic diameter; UD) to predict postoperative complications and patency. Methods: Sixty-three patients who underwent radiocephalic AVF creation and had measurements of UD and SD were retrospectively analyzed. Cutoff values for UD and SD regarding complications were used to dichotomize the patients into high and low groups for comparisons. Results: The 2-year primary and secondary patency rates overall were 66.5% and 88.9%, respectively. The optimal UD and SD cutoff values were 2.4 and 3.5 mm, respectively. The 2-year primary patency rate was higher in the high-SD group than the low-SD group (88.2% vs. 58.6%; p = 0.0426). The 2-year secondary patency rate was significantly higher in the high-UD/high-SD group than the low-UD/low-SD group (91.7% vs. 68.4%; p = 0.0067). Conclusions: Intraoperative measurement of vein diameter using dilators during AVF creation might be a useful method of predicting patency, particularly when SD is used in combination with UD.